Nitrite and Nitrate Levels in Follicular Fluid From Human Oocyte Donors Are Related to Ovarian Response and Embryo Quality - Staicu, Florentin-Daniel; Canha-Gouveia, Analuce; Soriano-Úbeda, Cristina; Martínez-Soto, Juan Carlos; Adoamnei, Evdochia; Chavarro, Jorge E.; Matás, Carmen (Frontiers in Cell and Developmental Biology, 2021)
Nitric oxide, a key regulatory molecule in the follicular fluid, has been suggested as a possible biomarker to predict ovarian response in stimulated cycles and the potential of the retrieved oocytes for developing high-quality embryos. Nevertheless, a consensus on whether or not nitric oxide can help in this context has not been reached. We simultaneously measured the oxidation products of nitric oxide, nitrite, and nitrate, via HPLC-UV/VIS in follicular fluid samples from seventy-two oocyte donors. We found no associations of follicular fluid nitrite, nitrate, total nitric oxide, or nitrate/nitrite ratio with total or MII oocyte yield. However, nitrite and nitrate levels were related to the yield of MII oocytes when this outcome was expressed as a proportion of all oocytes retrieved. The adjusted MII proportion in the lowest and highest nitrite levels were 68% (58-77%) and 79% (70-85%), respectively (p, linear trend=0.02); whereas the adjusted MII proportion in extreme tertiles of nitrate levels were 79% (70-85%) and 68% (57-77%) (p, linear trend=0.03). In addition, nitrate levels showed a suggestive inverse correlation with embryos with maximum or high potential of implantation (p-value=0.07). These results suggest that the follicular fluid concentrations of nitrite and nitrate may be a useful tool in predicting how healthy oocyte donors respond to superovulation and the implantation potential of the embryos produced from their oocytes.